The Relationship Between Brushing Teeth and Debris Index in Pregnant Women at The Buduran Health Center, Sidoarjo Regency - Bella Hidayatus Syafitri; Imam Sarwo Edi; Isnanto; Ida Chairanna Mahirawatie (International Journal of Advanced Health Science and Technology, 2024)
The average debris index in pregnant women at the Buduran Health Center, Sidoarjo Regency is in the bad category. The high debris index is caused by several factors from the way brushing teeth. During pregnancy, pregnant women are encouraged to always maintain oral hygiene, namely by brushing their teeth regularly and the right way to maintain the health of their personal teeth and mouth, so as to avoid oral diseases that can affect pregnancy. The purpose of this study is to find out relationship between brushing teeth and debris index in pregnant women at the Buduran Health Center, Sidoarjo Regency. This type of research is an analytical research with a cross sectional method with a sample of pregnant women at the Buduran Health Center, Sidoarjo Regency which totals 44 pregnant women. The data collection instruments used are examination sheets to measure the debris index and observation sheets to assess how to brush teeth. The analysis technique uses the Chi-Square test. The results of the research on how to brush the teeth of the pregnant women at the Buduran Health Center, Sidoarjo Regency are the medium category, which is 54.5%. The debris index of pregnant women at the Buduran Health Center, Sidoarjo Regency is included in the moderate category of 56.8%. The results from the study obtained a p value of 0.023 or a P score of significance below α (0.05). There is relationship between brushing teeth and debris index in pregnant women at the Buduran Healt Center, Sidoarjo Regency.